2020
DOI: 10.21512/bbr.v11i2.6241
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution Channel Preferences in Purchase Decision-Making of Backpacker Hostel Customers

Abstract: The research aimed to find the correlation between distribution channels to each purchase decision-making process in hostel buying. This research was quantitative research using questionnaires to gather the data from 349 respondents. Linear regression analysis was used to analyze the data to find the correlation between each variable. The result shows that Online Travel Agent (OTA) has a significant and positive relationship to every purchase decision-making process. Then, go-show has only a significant and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…Penelitian ini juga didukung oleh penelitian (Yunitasari & Hendarti, 2021) pada CV. Cakra Nusantara Sragen, penelitian (Hernanta, 2017) pada PT/ Unilever Tbk dan (Pramudita et al, 2020) pada Online Agent Travel.…”
Section: Pengaruh Manajemen Saluran Distribusi Terhadap Keputusan Pem...unclassified
“…Penelitian ini juga didukung oleh penelitian (Yunitasari & Hendarti, 2021) pada CV. Cakra Nusantara Sragen, penelitian (Hernanta, 2017) pada PT/ Unilever Tbk dan (Pramudita et al, 2020) pada Online Agent Travel.…”
Section: Pengaruh Manajemen Saluran Distribusi Terhadap Keputusan Pem...unclassified
“…The pattern of benefits is combed overseas, so that consumer interests are tested comprehensively. Both Pramudita et al (2020) and Azzadina et al (2012) found that decision making in renting a hotel is influenced by distribution channels. They also showed a positive correlation with industrial growth in the city of Bandung.…”
Section: Distributionmentioning
confidence: 99%
“…OTA menawarkan perubahaan layanan yang secara tradisional harus dilakukan secara go show diubah menjadi layanan diberikan secara online. OTA memberikan kemudahan kepada konsumen untuk dapat mengakses distribution channel yang disediakan oleh perusahaan melalui gadget yang mereka miliki dimanapun dan kapanpun (Pramudita, Bisma, & Guslan, 2020). Berdasarkan hasil survey yang dilakukan oleh SimilarWeb, terdapat beberapa kompetitor dari Traveloka di Indonesia.…”
Section: Gambar 2 Data Penetrasi Internet Dunia 2020unclassified